2019
DOI: 10.18632/aging.101986
|View full text |Cite
|
Sign up to set email alerts
|

circFADS2 protects LPS-treated chondrocytes from apoptosis acting as an interceptor of miR-498/mTOR cross-talking

Abstract: We aimed to investigate the regulation of circular RNAs in lipopolysaccharide (LPS)-treated chondrocytes isolated from SD rat. In this study, we analyzed how circFADS2 was regulated in LPS-treated chondrocytes and isolates from Rheumatoid arthritis (RA) patients and found that circFADS2 and mTOR were highly expressed whereas miR-498 expression was significantly reduced. We then silenced circFADS2 in LPS-treated chondrocytes; this resulted in a declined expression of type II collagen, but an increase in the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Consistently, circFADS2 can sponge miR-498 [13]. Interestingly, our data showed that circFADS2 could suppress the maturation of miR-15a-5p.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistently, circFADS2 can sponge miR-498 [13]. Interestingly, our data showed that circFADS2 could suppress the maturation of miR-15a-5p.…”
Section: Discussionsupporting
confidence: 83%
“…In another study, circFADS2 was reported to be upregulated in colorectal cancer and predicted the poor survival of patients [17]. Besides that, circFADS2 plays protective roles in LPS-treated chondrocytes by interacting with miR-498/mTOR axis [13]. In this study we rst showed the upregulation of circFADS2 in sepsis patients.…”
Section: Discussionmentioning
confidence: 50%
“…The data of this study were mainly obtained using LPS‐stimulated chondrocytes in vitro. Although LPS‐stimulated chondrocytes have been widely used as an in vitro model for the study of OA, this type of study cannot provide sufficient data to conclude that ABIN‐1 plays a vital role in the regulation of OA progression. Therefore, the precise role of ABIN‐1 in OA requires further validation using in vivo animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer and colorectal cancer, circFADS2 is overexpressed and promotes cancer progression by regulating cancer cell behaviors, such as increasing cell proliferation and invasion [18,19]. Besides that, a recent study reported that circFADS2 could interact with miR-498/mTOR axis to protect chondrocyte from LPS-induced apoptosis [15]. It is well known that LPS-induced cell apoptosis and in ammation are critical contributors to sepsis [17], indicating the involvement of circFADS2 in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, circRNAs are potential targets to treat diseases. It has been reported that circRNA circFADS2 and miR-133a play opposite roles in LPS-induced cell apoptosis [15,16], which contributes to the development of sepsis [17]. We therefore analyzed the involvement of circFADS2 and miR-133a in sepsis and explored the interactions between them.…”
Section: Introductionmentioning
confidence: 99%